Psychological Well-being of Women in Patriarchal Relationships Living in Rural Eastern Cape, South Africa - J.G. Kheswa; S. Mrwetyana; M.M.R Makupula; V.P.P Lupuwana; Happiness Okoka (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Patriarchy continues to escalate in many African countries and impairs psychological well-being of women due to intimate partner violence. This qualitative research tried to describe psychological well-being of women in patriarchal relationship. This study involved twelve women, aged, 20 -50 years old from one rural area in the Eastern Cape, South Africa, was conducted. Prior collecting data, by means of face-to-face interview, the researchers sought the permission from one university in the Eastern Cape. Lincoln and Guba’s principles namely, credibility, transferability, dependability and confirmability ensured trustworthiness as the researchers relied on the audio-taped to code and transcribed data into themes. Guided by Robert Agnew’s general strain theory and Ryff’s six dimensions of psychological well-being, the findings revealed that women who live with abusive sexual partners lack positive self- esteem, cannot negotiate safe sex and often hide their emotional inadequacy in drugs and alcohol abuse and finding solace in attending church. A holistic approach would be key because would be empowered and acquire skills for self- reliance, employability and assertiveness to stand for their human rights.